Connectivity of Neotropical River Basins in the Central Guiana Shield Based on Fish Distributions - de Souza, Lesley S.; Armbruster, Jonathan W.; Willink, Philip W. (Frontiers in Forests and Global Change, 2020)
The Guiana Shield in northeastern South America contains some of the largest tracts of intact forests on the globe. Guyana alone has more than 80% forest cover. In south-central Guyana a unique biogeographic feature allows for a hydrological connection between the Guiana Shield with the Amazon basin via the Rupununi savannas and wetlands (Rupununi Portal). This corridor allows for connectivity between two of the most biodiverse, carbon rich and intact forests in the world. The significance of this (and other) hydrological corridors for terrestrial and aquatic species are underappreciated in the scientific literature. We attempt to determine the importance of the surrounding mosaic of habitats that influence fish assemblages in the Rupununi Portal. We extensively sampled fishes in this corridor over six expeditions. Multivariate analyses revealed significant trends in fish assemblage structure and environmental conditions. We found high species richness and diversity within the Takutu (Amazon River drainage) and Rupununi rivers (Essequibo River drainage). Fish assemblages were found to be most similar within the specific river drainages with some similarity within forest and savanna sites. A second Rupununi portal was revealed in the South Rupununi, at the upper Rupununi and Takutu Rivers. Ordination analyses found water body type, vegetation and water chemistry to be significantly structuring the fish assemblages of the Rupununi. Our study reveals the interdependent nature of the various habitats in the Rupununi that facilitate high biodiversity and maintain the ecosystem. With the increase in human activity in this region, and the increased connectivity of the region with the rest of the world through better roads, this area is in danger of being modified and fragmented to a point where ecosystem services begin to fail. We recommend demarcating a protected area in the region that considers the diversity of associated habitats and the importance of the ecological portal joining two diverse river basins.